Capnocytophaga sputigena: An unusual cause of community-acquired pneumonia. (2019) - Gosse, Laurie; Amrane, Sophie; Mailhe, Morgane; Dubourg, Grégory; Lagier, Jean-Christophe
Highlights: Capnocytphaga sputigena is a commensal of the subgingival throat. Capnocytophaga sputigena is a rare cause of pneumonia. The boarder from commensal bacteria to pathogen bacteria is narrow. Abstract: Capnocytophaga sputigena is an unusual cause of community-acquired pneumonia. A 22-year-old woman presented an amoxicillin-resistant pneumonia. Sputum examination detected C. sputigena from 3 specimens with a significant bacterial load. The strain produced beta lactamase. Evolution was favorable after introduction of amoxicillin-clavulanate acid. Physicians might be aware of the presence of this unusual bacterium in cases of community-acquired pneumonia.